2022
DOI: 10.3390/fib10070056
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Effect of Fiber Length on Mechanical, Wear, and Morphological Behavior of Silane-Treated Pineapple Leaf Fiber Reinforced Polymer Composites

Abstract: The development of the best properties in polyester composite from pineapple leaf fiber (PALF) as a reinforcing material is a subject of interest. The properties of PALF are reliant upon fiber length, wherein technical difficulties in production of long fibers and processing for better characteristics in polyester composites possess inherent challenges. The PALFs are subjected to silane treatment for altering fiber properties. This research attempts to analyze the impact of silane-treated PALF with varying fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…Fiber length and wt% are the key factors for the interfacial bonding strength between the fiber and matrix material. The effect of pineapple leaf fiber length was studied by Anand et al 67 who concluded that 15–20 mm fiber length resulted in better fiber–matrix bonding, and improved fracture toughness as compared to the short fiber of 5–10 mm or long fiber of 25 mm. Chavan et al 68 studied the effect of fiber lengths of 10, 20, 30, 40, 50, and 70 mm on the tensile strength and found that the optimum tensile strength was observed for the fiber length 30 to 45 mm of sun hemp, banana, and Sisal fiber.…”
Section: Resultsmentioning
confidence: 99%
“…Fiber length and wt% are the key factors for the interfacial bonding strength between the fiber and matrix material. The effect of pineapple leaf fiber length was studied by Anand et al 67 who concluded that 15–20 mm fiber length resulted in better fiber–matrix bonding, and improved fracture toughness as compared to the short fiber of 5–10 mm or long fiber of 25 mm. Chavan et al 68 studied the effect of fiber lengths of 10, 20, 30, 40, 50, and 70 mm on the tensile strength and found that the optimum tensile strength was observed for the fiber length 30 to 45 mm of sun hemp, banana, and Sisal fiber.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, when composites are subjected to stress, interfacial voids may form and act as stress concentrators, leading to poor mechanical behavior 47 . Generally, larger fibers hinder matrix penetration between the fiber and resin spaces, resulting in low wetting characteristics and thus inefficient stress transfer at the matrix‐reinforcement interface 48 . Furthermore, when materials are exposed to service conditions, cracks expand around the fibers; therefore, the fracture surface area increases with particle size, causing reduced tensile properties 49 .…”
Section: Resultsmentioning
confidence: 99%
“…47 Generally, larger fibers hinder matrix penetration between the fiber and resin spaces, resulting in low wetting characteristics and thus inefficient stress transfer at the matrixreinforcement interface. 48 Furthermore, when materials are exposed to service conditions, cracks expand around the fibers; therefore, the fracture surface area increases with particle size, causing reduced tensile properties. 49 All of the above can be quantitatively reflected in the in OPEFB/vinyl acrylic composites-by means of the fraction not shared between the fiber length distributionsin at least 20.93% of OPEFB fibers retained on mesh no.…”
Section: Microbiological Testmentioning
confidence: 99%
“…Fiber-reinforced polymeric composites (FRPs), a typical lightweight engineering material with remarkable specific modulus and strength, heat insulation, corrosion resistance and shock absorption are increasingly favored in diversified fields, such as aerospace, civil engineering and automobile manufacturing [5,6] . Recently, graphene has been envisioned as the powerful building block for next-generation FRPs with the purpose of smart structures integration and multifunctional properties mastery [7,8] .…”
Section: Introductionmentioning
confidence: 99%